Pengaruh Live Streaming Shopping Dan Promosi Penjualan Terhadap Keputusan Pembelian Produk Fashion Pada Aplikasi Tiktok Shop Tahun 2023 - Amin, Muhammad Miftakhul; Taufiqurahman, Endang (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to understand the correlation, partial influence, and simultaneous influence of Live Streaming Shopping and Sales Promotion on Fashion Product Purchase Decisions on the TikTok Shop Application in 2023. The research method uses a descriptive and verification quantitative approach. The sample in this study was 385 respondents taken from the unlimited population of TikTok users in Indonesia using the Lemeshow formula. The sampling technique in this study used a non-probability sampling technique with a purposive sampling method. Data analysis in this research uses path analysis and hypothesis testing using the t test and f test. By using Microsoft Excel tools, Method of Successive Interval (MSI), and the SPSS application version 25. The results of the analysis of this study show that the correlation between Live Streaming Shopping and Sales Promotion is strong, with a coefficient of 0.652, which indicates a positive and significant relationship. Live Streaming Shopping has a partial effect of 26.2% on Purchase Decisions, while Sales Promotions has a partial effect of 35.1%. The simultaneous effect of Live Streaming Shopping and Sales Promotion on Purchasing Decisions is 61.4%, while the remaining 38.6% are other variables not examined in this study.